(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The proverb, which is considered one of the ancient examples of folklore, is different it is different from other genres due to its short, concise, figurative and deep content stands out. The ancient and rich spirituality of each nation through proverbs appears. Proverbs are extremely rich and diverse in terms of subject matter can be used literally or figuratively. For proverbs as an object, persons, things, and at the same time, animals are taken.